A new index for quantifying walking foot pressure patterns in Hansen's disease - Bhatia, M.M.; Patil, K.M. (1996 15th Southern Biomedical Engineering Conference, 1996)
The purpose of this work is to quantify the effects of various pathological conditions observed in Hansen's disease subjects on their barefoot walking foot pressure patterns. A new index called Contact Ratio Index (CRI), which takes into account the pressure and the time for which it acts, is used to compare foot pressure patterns of normals and Hansen's disease subjects. Foot pressure patterns are recorded using the optical pedobarograph. The feet are classified such that all feet in one class show similar clinical and radiological conditions. Results show that values of CRI in various regions of the foot reflect its clinical and radiological condition. Thus, CRI could possibly provide a quantitative insight into the condition of the foot to the clinician.